Crucial Role of Interferon-γ and Stimulated Macrophages in Cardiovascular Disease - Schroecksnadel, Katharina; Frick, Barbara; Winkler, Christiana; Fuchs, Dietmar (Current Vascular Pharmacology, 2006)
Inflammation and immune activation are crucially involved in the pathogenesis of atherosclerosis and cardiovascular disease. Accordingly, markers of inflammation such as fibrinogen, ferritin, C-reactive protein or neopterin are found in patients with vascular diseases, correlating strongly with the extent of disease and predicting disease progression. Neopterin formation by human monocyte-derived macrophages and dendritic cells is induced by the pro-inflammatory cytokine interferon-γ, which is released by activated T-lymphocytes. Human macrophages are centrally involved in plaque formation, and interferon-γ and macrophages are also of importance in the development of oxidative stress for antimicrobial and antitumoural defence within the cell-mediated immune response. Interferon-γ also stimulates the enzyme indoleamine- 2,3-dioxygenase, which degrades tryptophan to kynurenine. Again, macrophages are the most important cell type executing this enzyme reaction, but also other cells like dendritic cells, endothelial cells or fibroblasts can contribute to the depletion of tryptophan. Likewise, enhanced tryptophan degradation was reported in patients with coronary heart disease and was found to correlate with enhanced neopterin formation. In chronic diseases such as in cardiovascular disease, biochemical reactions induced by interferon-γ may have detrimental consequences for host cells. In concert with other pro-inflammatory cytokines, interferon-γ is the most important trigger for the formation and release of reactive oxygen species (ROS). Chronic ROS-production leads to the depletion of antioxidants like vitamin C and E and glutathione, with a consequence that oxidative stress develope. Oxidative stress plays a major role in the atherogenesis and progression of cardiovascular disease, and it may also account for the irreversible oxidation of other oxidation-sensitive substances like B-vitamins (e.g. folic acid and B12). They are essential cofactors in homocysteine-methionine metabolism. Associations between moderate hyperhomocysteinaemia and cellular immune activation are found in several diseases including coronary heart disease, and data indicate that hyperhomocysteinaemia may develop as a consequence of immune activation. Homocysteine accumulation in the blood is established as an independent risk factor for cardiovascular disease. Homocysteine itself has the capacity to further enhance oxidative stress. Interferon-γ appears to be a central player in atherogenesis and in the development and progression of cardiovascular disease. Anti-inflammatory and immunosuppressive treatment (e.g. with non-steroidal anti-inflammatory drugs or statins) may among other consequences, also contribute to a slow-down of the adverse effects of interferon-γ.
Keywords: homocysteine